ANALISIS PENGARUH ZAT GIZI TERHADAP KEJADIAN ANEMIA PADA REMAJA PUTRI DI SMA HANGTUAH KOTA TARKAN - Nur Indah Noviyanti Rahman (Jurnal Medika Hutama, 2023)
Adolescence is a period of transmission from children to adults. The changes that occurred during this period were clearly visible both physically and psychologically. At this time, there is not only growth to become bigger, but also reproductive development occurs. This period is characterized by rapid physical growth and development so that sufficient nutrients are needed to help optimize their growth and development. Every nutrient that is absorbed into the body of adolescents will increase weight and height, as well as increase the size and number of cells in the body. The need for energy and protein in adolescents becomes greater due to growth suprt (growth surge in adolescents). Not only physical and mental growth and development, but the activity of adolescents also increases so that they need foods that contain increased nutrients. young women in Tarakan City age group (10-24 years) namely 31,697 out of 245,701 inhabitants. Indonesia has great human resource (HR) potential for nation building. The nutritional status of adolescents in North Kalimantan is still an unresolved problem with 26.2% of adolescents being short and 4.7 adolescents being very short. If you look at the nutritional status of BMI in adolescents in North Kalimantan, that is 1.8% very thin, 6.1% thin, 78.8% normal, 9.3% fat and 4% obese. The most common nutritional problem in young women is iron deficiency which causes them to experience anemia. Hangtuah Senior High School has 450 students, with a total of 158 female students. The results of an initial survey conducted at Hangtuah Senior High School showed that 7 out of 10 students had anemia. Anemia can occur due to various factors, ranging from nutritional status, knowledge, family factors, environment, history of disease and physical activity. This study aims to determine the effect of nutritional status on the incidence of anemia in young women at Hangtuah Senior High School.